2013
DOI: 10.1002/ajmg.b.32214
|View full text |Cite
|
Sign up to set email alerts
|

Significant study of population stratification, sensitivity analysis and trim and fill analyses on GBA mutation and parkinson's disease

Abstract: This comprehensive meta-analysis was applied to case-control studies of the association between PD and GBA to assess the joint evidence for the association, the influence of individual studies, and evidence for publication bias. We searched PubMed, Medline, Cochrane Library, reference lists of relevant studies to June 2012, and email contact with authors. For the case-control studies, the authors found 1) support for the association between PD and GBA, both in total group analysis [fixed: OR and 95%CI: 4.825 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The study reported an overall odds ratio of 5.43 for carrying any GBA mutation in PD patients when compared with controls . The association between GBA mutations and PD has been confirmed in large‐scale comprehensive meta‐analyses . The GBA gene encodes for GCase, which catalyzes the conversion of glucosylceramide into glucose and ceramide.…”
Section: Lsds and The Emerging Role Of Lysosomal Dysfunction In Pdmentioning
confidence: 84%
See 1 more Smart Citation
“…The study reported an overall odds ratio of 5.43 for carrying any GBA mutation in PD patients when compared with controls . The association between GBA mutations and PD has been confirmed in large‐scale comprehensive meta‐analyses . The GBA gene encodes for GCase, which catalyzes the conversion of glucosylceramide into glucose and ceramide.…”
Section: Lsds and The Emerging Role Of Lysosomal Dysfunction In Pdmentioning
confidence: 84%
“…55 The association between GBA mutations and PD has been confirmed in large-scale comprehensive meta-analyses. 56,57 The GBA gene encodes for GCase, which catalyzes the conversion of glucosylceramide into glucose and ceramide. Aggregation of a-synuclein in brains from patients with GBA1-associated parkinsonism and the detection of GCase as a component of LBs in PD patients suggested that GCase dysfunction contributes to PD-like pathological inclusions.…”
Section: Lsds and The Emerging Role Of Lysosomal Dysfunction In Pdmentioning
confidence: 99%
“…Although parkinsonism is a rare feature in patients with GD, several GD patients with parkinsonism had relatives with a typical, late-onset form of PD [ 32 ]. After confirmation of this observation in large-scale multicenter studies [ 33 ] and meta-analyses [ 34 , 35 ], the presence of pathogenic heterozygous mutations in this gene is now considered as one of the most important risk factors to develop PD. It is estimated that the prevalence of PD patients with GBA mutations is 5–10%, while this percentage can be higher in certain populations [ 36 ].…”
Section: Converging Evidence For a Role Of Alp Dysfunction In Pdmentioning
confidence: 98%
“…Many studies have shown an increased frequency of GBA variants in PD compared to controls. [2][3][4] GBA variants were shown to confer a fiveto seven-fold increased risk of PD 4,5 and to modify PD manifestations, causing earlier age of onset, more severe cognitive dysfunction, and accelerated progression of the neurodegenerative process. [6][7][8] Concerning the mechanism relating GBA variants to PD, it has been suggested that either a chronic loss of enzymatic activity or a possible toxic gain of function of the mutated glucocerebrosidase results in lysosomal dysfunction and endoplasmic reticulum stress could contribute to disease pathogenesis.…”
mentioning
confidence: 99%